Power distribution network voltage control method and device based on photovoltaic access, terminal equipment and storage medium - YI YANG; XU ZHANPENG; MIAO LU; CHEN KUIYE; YANG CHENG; GU YICAN; ZHANG XINGZI; LIU HAOYI; YANG ZHENNAN (2025)
The invention discloses a photovoltaic access-based power distribution network voltage control method, a photovoltaic access-based power distribution network voltage control device, terminal equipment and a storage medium. Adjusting the reactive power output of a second distributed photovoltaic which is located on the same outgoing line with the first distributed photovoltaic of which the voltage exceeds the upper limit under the constraint, and then determining that the reactive power output of the second distributed photovoltaic reaches the limit value and the voltage of the first photovoltaic access point still exceeds the upper limit; adjusting the reactive power output of the first centralized photovoltaic under the constraint; and when it is determined that the reactive power output of the first centralized photovoltaic unit reaches the limit value and the voltage of the first photovoltaic access point still exceeds the upper limit, calculating an out-of-limit reactive capacity value of a main transform